2011
DOI: 10.1029/2010jd014542
|View full text |Cite
|
Sign up to set email alerts
|

Long-term energy flux measurements and energy balance over a small boreal lake using eddy covariance technique

Abstract: [1] Measurements of the energy balance components of a small boreal lake (area 0.041 km 2 , mean depth 2.5 m) in southern Finland were performed during four open water periods (April-October) in [2005][2006][2007][2008]. Turbulent fluxes of sensible and latent heat acquired using the eddy covariance technique were accompanied by net radiation and water heat storage measurements. In April the lake was near isothermal, whereas in May the development of a thermocline was enabled by dark water color and a sheltere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
264
6

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 194 publications
(306 citation statements)
references
References 67 publications
(94 reference statements)
35
264
6
Order By: Relevance
“…Therefore turbulent exchange is enhanced compared with stable stratification typically found over lake surfaces during daytime (e.g. Beyrich et al 2006;Nordbo et al 2011). …”
Section: Flux Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore turbulent exchange is enhanced compared with stable stratification typically found over lake surfaces during daytime (e.g. Beyrich et al 2006;Nordbo et al 2011). …”
Section: Flux Measurementsmentioning
confidence: 99%
“…They attribute this change to increasing precipitation as well as thawing permafrost and glacial melt due to rising mean annual temperatures, nevertheless the relative contribution of the balance components, especially the role of evaporation, is discussed controversially. Consequently, fluxes over lake surfaces on the Tibetan Plateau should not be neglected since various studies have shown the contribution of lakes to the regional energy balance and water cycle in different catchments around the world (Rouse et al 2005;Nordbo et al 2011). Until now, estimations of evaporation over lake surfaces on the Tibetan Plateau have been modelled using remote sensing or land surface observations as forcing Haginoya et al 2009), whereas no direct measurements of turbulent fluxes over a lake surface have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] There are a number of long-term eddy covariance measurements and process-based studies for the surface energy budget over inland waters [Blanken et al, 2000;Eaton et al, 2001;Blanken et al, 2003;Rouse et al, 2003;Oswald and Rouse, 2004;Rouse et al, 2005;Vesala et al, 2006;Assouline et al, 2008;Rouse et al, 2008;Tanny et al, 2008;Liu et al, 2009;Blanken et al, 2011;Liu et al, 2011;Nordbo et al, 2011;Liu et al, 2012]. It is noted that, however, most of these measurements were made over highlatitude lakes, such as Great Slave Lake [Blanken et al, 2000;Rouse et al, 2003] and Great Bear Lake [Rouse et al, 2008] in Canada, Lake Valkea-Kotinen in Finland [Vesala et al, 2006;Nordbo et al, 2011], and Lake Superior Spence et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that, however, most of these measurements were made over highlatitude lakes, such as Great Slave Lake [Blanken et al, 2000;Rouse et al, 2003] and Great Bear Lake [Rouse et al, 2008] in Canada, Lake Valkea-Kotinen in Finland [Vesala et al, 2006;Nordbo et al, 2011], and Lake Superior Spence et al, 2011]. Liu et al [2012] was the first to report an annual analysis of the surface energy budget over a large southern reservoir.…”
Section: Introductionmentioning
confidence: 99%